Cardiovascular risk, metabolic disturbances, and the choice of antihypertensive therapy - M. N. Mamedov; M. V. Stroeva; R. T. Didigova; E. A. Poddubskaya; M. N. Kovrigina (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study antihypertensive and metabolic effects of combined antihypertensive therapy with fixed doses of ACE inhibitor and thiazide-like diuretic (Noliprel®), in comparison with ACE inhibitor monotherapy (ramipril). Material and methods. The study included 44 men, aged 30-65 years, with Stage I-II arterial hypertension (AH) and at least one manifestation of metabolic disturbances (dyslipidemia, pre-diabetes, or hyperuricemia). All participants were divided into two groups: Group I received ramipril, and Group II was administered a combination of ACE inhibitor and thiazide-like diuretic (Noliprel®/ forte). Results. Medication doses were increased in patients who failed to achieve target blood pressure (BP) levels. At baseline and after 6 months of the treatment, all patients underwent BP and heart rate (HR) measurement, electrocardiography (ECG) at rest, and the assessment of lipid profile, fasting and post-load (2 hours) glucose, insulin resistance (IR) index, uric acid (UA) and potassium (К+), as well as total coronary risk level. Conclusion. In men with AH and metabolic disturbances, combined antihypertensive therapy with fixed doses of ACE inhibitor and thiazide-like diuretic, as well as ACE inhibitor monotherapy, demonstrated good antihyperten-sive effectiveness and no deterioration in metabolic parameters. Combined antihypertensive therapy was associated with a reduction in coronary risk by 30 %.